Development of nanostructured lipid carriers as a promising tool for methotrexate delivery: physicochemical and in vitro evaluation. Issue 7 (3rd May 2023) - Rathee, Jyoti; Kanwar, Rohini; Kumari, Laxmi; Pawar, Sandip V.; Sharma, Shikha; Ali, Md. Ehesan; Salunke, Deepak B.; Mehta, Surinder Kumar
Abstract: The aim of the present study is to fabricate the stable nanostructured lipid carriers (NLCs) using biocompatible excipients for the encapsulation of Methotrexate (MTX), a chemotherapeutic agent for breast cancer treatment. MTX has restricted clinical applications owing to its low solubility, non-specific targeting and adverse side effects. Glyceryl Monostearate (GMS) and Miglyol 812 (MI1) were chosen as solid and liquid lipids, respectively, for the fabrication of NLCs, and the influence of variation of solid and liquid composition was investigated. The prepared NLCs exhibited long-term stability and spherical shape morphology as characterized by electron microscopy. The internal structure of fabricated NLCs was arranged into cubic crystalline as confirmed by small-angle X-ray scattering (SAXS) analysis. MTX's encapsulation efficiency of ∼85 ± 0.9%. and sustained in vitro release of MTX ∼ 52% ± 3.0 in 24 h was achieved. Classical molecular dynamics (MD) simulations were performed to study the structural stability of the MTX encapsulated NLCs. Hemolysis carried out on the NLCs showcased the biosafety of the formulation under the tolerance limit (<10%). Further, the MTT assay demonstrates that MTX-loaded NLCs exhibited toxicity against HeLa and MCF-7 cell lines as compared to blank NLCs. The finding demonstrates NLCs as promising vehicles for MTX delivery to address cancer. Communicated by Ramaswamy H. Sarma Graphical abstract: UF0001